Atlantis, the lost empire [videorecording (DVD)] - Trousdale, Gary; Wise, Kirk; Fox, Michael J., 1961-; Garner, James. 1928-2014; Summer, Cree; Novello, Don; Morris, Phil, 1959- (Distributed by Buena Vista Home Entertainment, 2002)
Hidden deep below the ocean surface is one of the greatest mysteries of all time--the Lost City of Atlantis. Join the world's most highly qualified crew of experts led by "adventure capitalist" Commander Rourke (Garner) and Milo Thatch (Fox), a linguist who knows the ancient Antlantean language, as they board the incredible 1,000-foot submarine, the Ulysses, and head deep into the mysteries of the sea, hoping to reveal the secrets of Atlantis.